1988
DOI: 10.3109/02841868809093557
|View full text |Cite
|
Sign up to set email alerts
|

Postoperative Management of Primary Spinal Cord Ependymomas

Abstract: Treatment and final outcome of 11 patients with primary spinal cord ependymomas admitted between 1967 and 1983 have been reviewed. All patients had undergone surgery once or twice before radiation treatment. Six of them are alive and disease-free 78 months to more than 180 months after radiation therapy. A short analysis of the recent literature is presented with special emphasis on the most frequent treatment techniques, extension of radiation fields and doses. The value of postoperative radiation therapy and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
15
0

Year Published

1992
1992
2015
2015

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 40 publications
(15 citation statements)
references
References 17 publications
0
15
0
Order By: Relevance
“…10,29 It is widely accepted that the first-line therapy for spinal cord ependymoma is surgery. 3,4,6,7,9,13,15,16,[18][19][20]23,24,26,27,31,32,34,35,38,41,43 Modern microsurgical techniques have resulted in a greater percentage of GTRs. Although anaplastic ependymomas are more aggressive than classic ependymomas, Prayson et al 33 found that anaplastic ependymomas, like lower-grade ependymomas, tended to be well demarcated from the surrounding spinal cord, rather than diffusely infiltrative.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…10,29 It is widely accepted that the first-line therapy for spinal cord ependymoma is surgery. 3,4,6,7,9,13,15,16,[18][19][20]23,24,26,27,31,32,34,35,38,41,43 Modern microsurgical techniques have resulted in a greater percentage of GTRs. Although anaplastic ependymomas are more aggressive than classic ependymomas, Prayson et al 33 found that anaplastic ependymomas, like lower-grade ependymomas, tended to be well demarcated from the surrounding spinal cord, rather than diffusely infiltrative.…”
Section: Discussionmentioning
confidence: 99%
“…Distinct from lesions that result from dissemination of intracranial anaplastic ependymomas and recurrent or metastatic spinal anaplastic ependymomas, PSAEs have been described in the past only in case studies 5,11,22,30,32,39 or as part of a series of spinal cord ependymomas. 3,4,7,15,26,31,41,43 Accordingly, the clinical characteristics and treatment outcomes of PSAEs have not been emphasized and are less well understood than those of benign or classic ependymomas (WHO Grade II). Given the relative paucity of literature addressing the primary spinal anaplastic variant, we review our experience with these tumors, with analysis of their clinical presentation, radiographic imaging, surgery, complications, recurrence, and survival.…”
mentioning
confidence: 99%
“…42 Neither study provided statistical analyses stratified by tumor grade. In the adult literature, the role of adjuvant radiation in the management of spinal ependymomas is also a matter of debate: some studies recommend postoperative radiation therapy in cases of STR but not GTR, 18,40,41,65,66 others advocate for postoperative radiation therapy after GTR, 38 and some maintain that radiation is not indicated regardless of degree of resection. 20,26,42 Further studies are needed to determine the optimal management of these rare tumors.…”
Section: Surgery and Adjuvant Radiation Therapymentioning
confidence: 99%
“…7,42,62 Maximal resection is generally agreed to be the cornerstone of treatment for pediatric spinal ependymomas; 2,7,8,34,42,47,50 however, the addition of adjuvant radiation therapy after surgery is the subject of more debate. 2,7,8,48 While there are many studies on spinal ependymomas in adults, 11,12,[16][17][18]21,24,25,38,41,45,51,56,57,61,65 there are few papers on these tumors in children, and those that do exist tend to be small, single-institution retrospective studies that are not powered for statistical analysis stratified by tumor grade. 2,8,13,22,27,42,47,53 The goal of this paper is to use the nationally representative Surveillance Epidemiology and End Results (SEER) database to offer a population-based perspective on pediatric Grade II spinal ependymomas.…”
mentioning
confidence: 99%
“…Whereas the traditional attitude does not support the use of extensive surgery, but only a single biopsy or dural decompression followed by radiotherapy [27,31], at the present time a growing number of authors advocate aggressive surgical management, which seems to improve local control and survival [8,[16][17][18][19]21]. This was first achieved with ependymomas: most authors reported the difference in the subsequent course between patients with total removal of the tumor and those with subtotal or partial resection, with a high recurrence rate in those with incomplete removal [10,13,23,33,41]. Although conclusions are more controversial for astrocytomas, which constitute tumors more often infiltrating than displacing the surrounding neural tissue, several investigators agree that radical excision is associated with better long-term prognosis, when carried out before there is significant disability [8, 16-19, 21, 45].…”
Section: Discussionmentioning
confidence: 99%